Decision Support System for Determining Inventory and Sales of Goods Using Economic Order Quantity Methods and Linear Regression - Manaf, Khaerul; Cecep Nurul, Alam; Subaeki, B; Khaffah, M.F.; Ira, Rupaida; Aedah, Abd Rahman (2020)
Inventory control and sales are important activities for the company to run. Errors in determining the inventory of goods can cause swelling in operational costs so that the company experiences losses. To overcome this problem, a Decision Support System (DSS) is needed that can help make decisions in determining inventory and sales of goods. In this case, the researcher uses the Economic Order Quantity (EOQ) EOQ provides a reference regarding the number of purchases or orders of goods with minimum cost. Meanwhile, to determine the number of future sales, researchers used the Linear Regression method, which looks at the relationship between sales as a response variable and the sales period as a predictor variable. The results of this study can be used to estimate the amount of quantity each time order of goods and predict the number of sales in the next period.